Human Telomerase Reverse Transcriptase (hTERT) Expression in Patients with Chronic Myelogenous Leukemia at Different Phases of the Disease - K Alimoghadam; N Eynolahi; Y Mortazavi; Sh Rostami; SH Ghaffari; A Amini; Y Gahani; A Ghavamzadeh (Tehran University of Medical Sciences, 2008)
Background and Aim: Chronic Myelogenous Leukemia (CML) is a clonal hematopoietic stem cell disorder characterized by a translocation between chromosome 9 and 22 called Philadelphia Chromosome. Telomerase- essential enzyme that adds telomeric repeats into the telomeres- maintains integrity of chromosomal ends. Most normal somatic cells do not express hTERT (catalytic subunit of telomerase) but most neoplasia and cancer cells express it. In this study we evaluated the hTERT expression in patients with CML at different phases of the disease.Materials and Methods: In this cross sectional study, 73 samples of 45 patients with CML were studied. Twenty six of samples were taken from patients in chronic phase before therapy and 26 samples three month after therapy. Nine samples were taken in accelerated phase and 12 in blastic phase. hTERT expression was studied by RT-PCR and the results were analyzed using SPSS 15.Results: Thirty three (73%) of patients were male and 12 (23%) were female. Patients were divided into three age groups; 17-29, 30-40 and 41-75 years. Of 73 samples, 43 samples (58.9%) were positive for hTERT and 30 samples (41.1%) were negative for this gene. In chronic phase (before therapy) 69.2% of the samples were PCR positive, but after therapy only 38.5% of samples were PCR positive. In accelerated and blastic phases, 55.6% and 83.3% of samples were PCR positive respectively. The hTERT positivity was differently significant (p<0.05) among different phases of the disease.Conclusion: Significant difference between hTERT expression in different phases of CML disease can be used as a useful molecular marker for fallowing up, prognosis and disease progression after treatment.